If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 15 = 3(c + 5) Reorder the terms: 15 + 3x = 3(c + 5) Reorder the terms: 15 + 3x = 3(5 + c) 15 + 3x = (5 * 3 + c * 3) 15 + 3x = (15 + 3c) Add '-15' to each side of the equation. 15 + -15 + 3x = 15 + -15 + 3c Combine like terms: 15 + -15 = 0 0 + 3x = 15 + -15 + 3c 3x = 15 + -15 + 3c Combine like terms: 15 + -15 = 0 3x = 0 + 3c 3x = 3c Solving 3x = 3c Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '3'. x = c Simplifying x = c
| -66=-16-6x | | 312+12=36w | | 3x-5=2(2x+2)-9 | | -2(5-3H)=-34 | | 5(y+4)=7y+20 | | 90g^2-62g+16=0 | | 2(2x+3)=3x+6+x | | 8+6x-8x=16-8x | | q+3(q+2)=18 | | 5x-18+4x=-36 | | 7(x)(x+2)=29 | | 312+12w=36 | | 16y-14y=10 | | 0.07(7t+6)=0.49(t+2)-0.56 | | f(x)=5x^2+30x+49 | | 63=3x+5x-1 | | 63=3(3v+3) | | 9x^2-64x=0 | | X-4y-z=-3 | | -2+0=-9 | | 2-8k-6=2+8k-5k | | 4x-8=12+16x | | x+8+x=0 | | 5y+7=y+20 | | 3(q-5)=q+5 | | 4(w-9)7w=52 | | findc-3b+ac=c | | 5t-8= | | -4+2x+6x=68 | | 15-5x=8x-24 | | 1500(3)+125x=2125 | | x(5x+11)=2x^2-8x |